Socio-Religious-Based Critical Digital Media Literacy for Disengagement from Radicalism for Ex-Terrorist Convicts - Faiqotul Mala; Fazlul Rahman; Ema Marhumah; Agung Danarta (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article aims to analyze the influence of the Internet on the involvement of former terrorist prisoners, as well as formulate a Socio-Religious-based Digital Media Literacy model that can support the process of disengagement from radicalism. To help this research provide a comprehensive picture, this study interviewed one female former terrorist inmate and her companion after being released from prison, as well as a representative from Ruangobrol.id. This organization cares for former terrorist inmates to become